Perlindungan Hukum Bagi Anak Korban Kekerasan Seksual di Lingkungan Sekolah - Hasanah, Nur; Yuspin, Wardah (Jurnal Ilmu Sosial dan Humaniora, 2026)
Sexual violence against children in schools has become a public focus. Schools, which are supposed to be places for learning and educating children to become educated individuals, are instead used by some teachers or educators to fulfilll their desires. Therefore, children as victims need to be given legal protection. The role of teachers in schools, who are supposed to be parents, should not be that of perpetrators of sexual violence. The first problem focus to be discussed is the effectiveness of protecting children who are victims of sexual violence in the school environment according to laws and regulations. The second is child protection efforts for victims of sexual violence in the school environment. This paper aims to analyze and assess the effectiveness of legal protection regulations for children as victims of sexual violence in the school environment based on Law Number 35 of 2014 concerning Child Protection. Second, to identify and examine the forms and efforts of legal protection provided to victims. This research uses a normative legal research method that employs legal material collection methods, literature studies, or document studies. The results of this study show that legal protection for children is already regulated in Law Number 35 of 2014, but this law has not been implemented optimally due to obstacles. Therefore, legal protection for children in the school environment requires preventive and repressive efforts, as well as cooperation between the government and the community